Savoirs locaux et adaptation au changement climatique au mayo-kebbi est entre 1990-2020 - Esaïe MASSANA DOUM (Revue Hybrides)
Climate change is a natural phenomenon that threatens the existence of human beings. It is a phenomenon that has a considerable impact on populations experiencing significant rapid changes, plunging rural populations into poverty and chronic food insecurity. This study deals with the local manifestations of these changes in Mayo-Kebbi Est in Chad between 1990-2020. To properly conduct this study, we adopted a methodological approach. The methodology used was a combination of quantitative and qualitative approaches. In the seven villages selected, a sample of 120 farms was constituted. Individual questionnaires and group interview guides are the tools used to process information. The software used is Excel (2007), SPSS (16.0) and SAS (9.1) for statistical tests were also used. After compiling the data, the survey carried out among a sample composed of farmers, breeders and fishermen allowed us to note that these populations are very vulnerable to the harmful effects of climate change, which have socio-economic consequences (decrease in agricultural yields, food insecurity, lack of drinking water etc.). Research findings show that climate change poses challenges. Finally, at the local level, the challenges of climate change relate to the development of the most appropriate and effective strategies. Because it is in the countryside that the impacts are felt the most. However, the knowledge produced in relation to climate change and its effects will only produce the expected effects if it guides and fuels development policies and actions.